STRATEGI KOMUNIKASI PEMASARAN SHERATON HOTEL LAMPUNG PADA MASA PANDEMI COVID-19 - Achmad Kanzulfikar (Universitas Sumatera Selatan, 2022)
Sheraton Hotel Lampung is a company engaged in hospitality services, has a market share of domestic and foreign tourists. The Covid-19 pandemic has caused the Sheraton Hotel Lampung to experience a decrease in visitor occupancy rates. Experiencing this decline, Sheraton Hotel developed and implemented a Marketing Communication Strategy as a step to increase occupancy again. The purpose of this research is to find out the marketing communication strategy of Sheraton Hotel Lampung during the Covid-19 Pandemic. The theory used in this study is Belch & Belch's marketing communication strategy which explains that a process of marketing communication strategy has a detailed and systematic plan. This study used a qualitative descriptive type approach and case study method, data collection techniques namely interviews, observation and documentation. The results of the study found that the Sheraton Lampung Hotel compiled a pattern of marketing communication strategies starting from the research stage, review, the situation of the marketing communication program, the communication process, determining the budget, the implementation of the marketing communication program at this stage the Sheraton Lampung Hotel used elements from the promotion mix including namely, Advertising, Personal Selling, Sales Promotion, Publicity, and Digital/Internet marketing, as well as updating promotional programs in order to increase the number of guest visits to Sheraton Hotel Lampung.